Rethinking incarceration : advocating for justice that restores - Gilliard, Dominique DuBois, 1984- (Downers Grove : InterVarsity Press, 2018)
Explores the history and foundation of mass incarceration and examines Christianity's role in its evolution and expansion. Shows how Christians can pursue justice that restores and reconciles, and offers creative solutions and innovative interventions to help bring authentic rehabilitation, lasting transformation, and healthy reintegration to America's broken criminal justice system.
Part 1. The roots and evolution of mass incarceration. The war on drugs -- How did we get here? From black codes to neoslavery -- Beyond law and order -- Three overlooked pipelines: mental health, private prisons, and immigration -- The school-to-prison pipeline -- Part 2. The church's witness and testimony. Protestant reformers: prophetic activism, nonviolence, and God's wrath -- The prisoners' pastor: chaplaincy and theology's institutional impact -- The spirit of punishment: atonement, penal substitution, and the wrath of God -- Atonement and sanctifying retribution -- Divine justice is inherently restorative -- Holy interruptions: dismantling mass incarceration.
Includes bibliographical references.
Keywords: Christianity and justice -- United States; Discrimination in criminal justice administration -- United States; Imprisonment -- United States; Jails -- United States